2011
DOI: 10.1186/1756-0500-4-455
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of Ureaplasma diversum in bovine spermatozoids

Abstract: BackgroundUreaplasma diversum has been associated with infertility in cows. In bulls, this mollicute colonizes the prepuce and distal portion of the urethra and may infect sperm cells. The aim of this study is to analyze in vitro interaction of U. diversum isolates and ATCC strains with bovine spermatozoids. The interactions were observed by confocal microscopy and the gentamycin internalization assay.FindingsU. diversum were able to adhere to and invade spermatozoids after 30 min of infection. The gentamicin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 27 publications
(44 reference statements)
0
27
0
1
Order By: Relevance
“…Presence of M. agalactiae was demonstrated in the standard HeLa cells, as well as in two different ruminant cell lines, namely BEND and BLF, using the quantitative gentamicin invasion assay and the qualitative visual method of double immunofluorescence staining. Though the highest invasion frequency of M. agalactiae is calculated to be around 2.3% at 24 h post infection, it is comparable and even better than the reported invasion frequencies of some other pathogens, especially mycoplasmas ( Martin and Mohr, 2000; Cieri et al, 2002; Dusanic et al, 2009; Marques et al, 2010; Buzinhani et al, 2011 )…”
Section: Discussionmentioning
confidence: 58%
“…Presence of M. agalactiae was demonstrated in the standard HeLa cells, as well as in two different ruminant cell lines, namely BEND and BLF, using the quantitative gentamicin invasion assay and the qualitative visual method of double immunofluorescence staining. Though the highest invasion frequency of M. agalactiae is calculated to be around 2.3% at 24 h post infection, it is comparable and even better than the reported invasion frequencies of some other pathogens, especially mycoplasmas ( Martin and Mohr, 2000; Cieri et al, 2002; Dusanic et al, 2009; Marques et al, 2010; Buzinhani et al, 2011 )…”
Section: Discussionmentioning
confidence: 58%
“…because secretory IgA plays a protective role in the vaginal mucosa . U. diversum has been associated with infertility in cows and may result in severe placentitis, fetal alveolitis, abortion and internalization into bovine blastocyst . U. parvum can be internalized into HeLa cells and can escape host cellular autophagosomal degradation by disturbing intracellular organisms through an unknown mechanism …”
Section: Genital Ureaplasma Infection and Preterm Birthmentioning
confidence: 99%
“…However, the damage to the host may be related to the site of infection. Studies show that colonization of the reproductive tract is commonly associated with infertility, abortions, premature births and lung injury in neonates (Ruhnke et al 1984, Murray 1991, Buzinhani et al 2011. In other mycoplasma species, such as U. urealyticum, was observed that the presence of bacteria in the respiratory tract of infants stimulates an increasing total number of white blood cells (Viscardi et al 2002).…”
Section: Discussionmentioning
confidence: 99%